2021
DOI: 10.1002/acr.24635
|View full text |Cite
|
Sign up to set email alerts
|

Using Critical Race Theory to Understand Trial Participation Among Black Individuals With Systemic Lupus Erythematosus: A Qualitative Study of Patients and Caregivers

Abstract: Objective Black patients with systemic lupus erythematous (SLE) experience greater disease incidence and severity than White patients, and yet they are underrepresented in SLE clinical trials. We applied Critical Race Theory to qualitatively explore the influence of racism on the underrepresentation of Black patients in SLE clinical trials and to develop a framework for future intervention. Methods We conducted focus group sessions in Chicago and Boston with Black adults (ages ≥18 years) with SLE and their car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Specifically, scores significantly improved on the topics of informed consent, the fact that standard of care is continued in control groups, and the Belmont Report's ethical guidelines for research conduct (Table 3 ). This improvement is meaningful, considering individuals' comfort with those topics had previously been noted to influence clinical trial participation ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Specifically, scores significantly improved on the topics of informed consent, the fact that standard of care is continued in control groups, and the Belmont Report's ethical guidelines for research conduct (Table 3 ). This improvement is meaningful, considering individuals' comfort with those topics had previously been noted to influence clinical trial participation ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
“…Qualitative research has illuminated several factors that contribute to racial disparities in clinical trial participation. Black patients with lupus have identified mistrust of medical and research systems due to experiences of racial discrimination ( 11 ). Other barriers include lack of familiarity with clinical trials, an intimidating consent process, strict exclusion criteria, and concerns about receiving a placebo or a drug with unknown side effects ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[99][100][101] Further, consciously making efforts to include disenfranchised groups of people in the research process may address the lack of inclusion of people of color in clinical trials. 102 Additionally, our review found that most race-related investigations focused on Black and White people. Fewer investigations focused on Latino/health outcomes, and no articles explicitly focused on AI/AN populations, despite AI/AN people having the worst SLE health outcomes.…”
Section: Clinical Practicementioning
confidence: 99%
“…4,[14][15][16][17][18] Improved patient-clinician communication can in turn increase trust in the clinician, build rapport, and improve patients' consideration of participation in lupus clinical trials 5,19,20. Conclusions Improving equity in patients' opportunities to participate in lupus clinical trials is essential to address disparities in clinical trial participation, and ultimately improve health outcomes.…”
mentioning
confidence: 99%